Lietuvių inteligentų socialinis vaidmuo formuojant tautinės tapatybės modelius kultūrinėje spaudoje - Linkevičiūtė-Rimavičienė, Jolita (Information & Media, 2011)
Nagrinėjamas inteligentijos vaidmuo formuojant viešąją nuomonę ir kuriant tapatybės modelius kultūrinėje spaudoje, Lietuvos tautinių atgimimo sąjūdžių laikotarpiais. Analizuojant socialinį fenomeną – kaip spauda dalyvauja aktyvinant kaitos procesus – taikomas aiškinamasis tyrimas, kokybinės analizės, lyginamasis ir interpretacinis metodai, atliekama literatūros apžvalga.Pagrindiniai žodžiai: kaita, inteligentai, tapatybė, kultūrinė spauda.The Role of Lithuanian Intelligentsia in Establishing the Identity ConstructsJolita Linkevičiūtė-RimavičienėSummaryThe article reviews the role of intelectuals in shaping the public opinion in Lithuania during the period of national revival movements and national consciousness development during political, social and economic changes in the public sphere, when in a revolutionary way the repressive regime is being destroyed and democracy begins developing, almost without a certain historical framework. When analysing in the media aspect, it becomes important that the nature and interpretation of information and reality are truthful when people are being mobilized for social changes, as are also social elite regulation, relevant for the implementation of the new goals and concepts.Historically, the cultural and political revival of the Lithuanian press is associated with the concept of freedom: freedom of speech, which arouses pepole’s awareness – raising and dissemination of national identity and publications as the national statehood, self-esteem and the idea of implementing measures of publishing and spreading advanced experience. When analysing the importance of culture publications in the periods of a social and political crisis, the role of intelectuals manifests itselfs. Academia and culture representatives become the editors of actual publications, and the limited periodicals are first of all vivifying and reconstructing historical memory and ethnic cultural heritage, identifying the revoliutionary situation and fulfilling the self-monitoring, self-observing function. Finding the connections between the previous periods of national liberation and their intellectual leaders is actual while analysing the significance of culture publications and their impact on the historical and social breaks.Keywords: intelligentsia, social changes, cultural periodics, identityx;">